Emerging Nanomedicines for the Treatment of Atopic Dermatitis - Parekh, Khushali (AAPS PharmSciTech, 2021)
Globally, the prevalence of Atopic dermatitis (AD) is significantly increasing and affecting around 20% of population including children. Complex interactions amongst abnormality in epidermal barrier function, environment, infectious agents and immunological defects are considered as key factors in the pathogenesis of AD. Although the role of oxidative stress has been studied in some skin diseases, investigation of the same in AD is intermittent. Calcineurin inhibitors and/or topical corticosteroids are currently available; however, it causes atrophy of the skin, burning sensation, and systemic side effects which leads to poor patient compliance. These limitations provoke the strong need to develop an innovative approach in managing AD. Nanomaterials for effective drug delivery to skin conditions such as AD have attracted a lot of attention owing to its ability to encapsulate, protect, and release the cargo at the diseased skin site. However, there are lots of unmet challenges especially in terms of development of non-toxic formulations and clinical translation of established nanomedicines in the form of accessible products. Numerous formulations have emerged as carrier for poorly soluble and permeable drugs, viz., lipidic, polymeric, metal, silica, liposomes, hydrocarbon gels and this field is evolving. This review is intended to provide an insight incidences associated with pathophysiology of AD and challenges with existing treatments of AD. Focus is kept on reviewing current development and emerging nanomedicines for effective treatment of AD. The review also inculcates merits of several nanomedicines in overcoming challenges of existing products and its future implications.